Computer Science and Its Applications : 5th IFIP TC 5 International Conference, CIIA 2015, Saida, Algeria, May 20-21, 2015, Proceedings - Amine, Abdelmalek; Bellatreche, Ladjel; Elberrichi, Zakaria; Neuhold, Erich J.; Wrembel, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 5th IFIP TC 5 International Conference on Computer Science and Its Applications, CIIA 2015, held in Saida, Algeria, in May 2015. The 56 revised papers presented were carefully reviewed and selected from 225 submissions. The papers are organized in the following four research tracks: computational intelligence; security and network technology; information technology; and software engineering.
Binary Bat Algorithm: On the Efficiency of Mapping Functions When Handling Binary Problems Using Continuous-Variable-Based Metaheuristics -- Relative Timed Model for Coordinated Multi Agent Systems -- A Novel Technique for Human Face Recognition Using Fractal Code and Bi-dimensional Subspace -- A New Rotation-Invariant Approach for Texture Analysis -- Multi-CPU/Multi-GPU Based Framework for Multimedia Processing -- Full-Reference Image Quality Assessment Measure Based on Color Distortion -- Biomarker Discovery Based on Large-Scale Feature Selection and MapReduce -- Social Validation of Solutions in the Context of Online Communities: An Expertise-Based Learning Approach -- Remotely Sensed Data Clustering Using K-Harmonic Means Algorithm and Cluster Validity Index -- Comparison of Automatic Seed Generation Methods for Breast Tumor Detection Using Region Growing Technique -- IHBA: An Improved Homogeneity-Based Algorithm for Data Classification -- Multiple Guide Trees in a Tabu Search Algorithm for the Multiple Sequence Alignment Problem -- Noise Robust Features Based on MVA Post-Processing -- Arabic Texts Categorization: Features Selection Based on the Extraction of Words Roots -- Restoration of Arabic Diacritics Using a Multilevel Statistical Model -- A New Multi-layered Approach for Automatic Text Summaries Mono-Document Based on Social Spiders -- Building Domain Specific Sentiment Lexicons Combining Information from Many Sentiment Lexicons and a Domain Specific Corpus -- Improved Cuckoo Search Algorithm for Document Clustering -- Supporting Legal Requirements in the Design of Public Processes -- Requirement Analysis in Data Warehouses to Support External Information -- Engineering the Requirements of Data Warehouses: A Comparative Study of Goal-Oriented Approaches -- Research and Analysis of the Stream Materialized Aggregate List -- SOLAP On-the-Fly Generalization Approach Based on Spatial Hierarchical Structures -- QoS-Aware Web Services Selection Based on Fuzzy Dominance -- A Hybrid Model to Improve Filtering Systems -- Towards a Recommendation System for the Learner from a Semantic Model of Knowledge in a Collaborative Environment -- Toward a New Recommender System Based on Multi-criteria Hybrid Information Filtering -- A New Approach for Combining the Similarity Values in Ontology Alignment -- Defining Semantic Relationships to Capitalize Content of Multimedia Resources -- A Multi-agents Intrusion Detection System Using Ontology and Clustering Techniques -- On Copulas-Based Classification Method for Intrusion Detection -- On-Off Attacks Mitigation against Trust Systems in Wireless Sensor Networks -- A Real-Time PE-Malware Detection System Based on CHI-Square Test and PE-File Features -- Balanced and Safe Weighted Clustering Algorithm for Mobile Wireless Sensor Networks -- Distributed Algorithm for Coverage and Connectivity in Wireless Sensor Networks -- Optimizing Deployment Cost in Camera-Based Wireless Sensor Networks -- A Version of LEACH Adapted to the Lognormal Shadowing Model -- High Velocity Aware Clocks Synchronization Approach in Vehicular Ad Hoc Networks -- An Energy-Efficient Fault-Tolerant Scheduling Algorithm Based on Variable Data Fragmentation -- Genetic Centralized Dynamic Clustering in Wireless Sensor Networks -- Region-Edge Cooperation for Image Segmentation Using Game Theory -- Improved Parameters Updating Algorithm for the Detection of Moving Objects -- Towards Real-Time Co-authoring of Linked-Data on the Web -- A High Level Net for Modeling and Analysis Reconfigurable Discrete Event Control Systems -- Hybrid Approach for Metamodel and Model Co-evolution -- Extracting and Modeling Design Defects Using Gradual Rules and UML Profile -- An Approach to Integrating Aspects in Agile Development -- On the Optimum Checkpointing Interval Selection for Variable Size Checkpoint Dumps -- Monitoring Checklist for Ceph Object Storage Infrastructure -- Towards a Formalization of Real-Time Patterns-Based Designs.
Keywords: Computer science; Software engineering; Artificial intelligence; Information systems; Engineering; Computer Applications; Software Engineering/Programming and Operating Systems; Artificial Intelligence; Information Systems and Communication Service; Computational Intelligence